2008
DOI: 10.1111/j.1468-1331.2008.02261.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of IL‐12 and TNF‐α in AIDP and AMAN

Abstract: Our data suggest that IL-12 promotes disease development in AIDP and in contrast to previously inflammatory assumptions, TNF-alpha may play double roles in GBS. The anti-inflammatory role of TNF-alpha realized through TNFR2 in AMAN is possibly a therapeutic mechanism in the IVIg treatment of AMAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Th1 and its cytokines are the pathogenic molecules in GBS as we reported previously [7, 8]. In the present study, we found that Th17 and Th22 cells and their cytokines may also contribute to the pathogenesis of GBS.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Th1 and its cytokines are the pathogenic molecules in GBS as we reported previously [7, 8]. In the present study, we found that Th17 and Th22 cells and their cytokines may also contribute to the pathogenesis of GBS.…”
Section: Discussionsupporting
confidence: 86%
“…The pathogenesis of GBS remains still enigmatic, but it is largely accepted that both cellular and humoral immune responses are involved in the pathogenesis of GBS [5, 6]. AIDP and its animal model experimental autoimmune neuritis (EAN) have hitherto been classified to Th1 cells-mediated disorders [79]. Th1 cells, a subset of CD4 + T (T helper) cells, are dominant in the inflamed nerves at the acute phase of GBS [8], which could produce IFN- γ as a major pathogenic cytokine in GBS, because increased IFN- γ was seen in the serum of GBS patients at acute phase [10], and higher immunoreactivity for IFN- γ was showed in sural nerves biopsies of GBS patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…4A,E). The inflammatory mediator TNF-a plays a key role in the pathological processes of Guillain-Barré syndrome and CIDP (Radhakrishnan et al, 2004;Deng et al, 2008;Yang et al, 2008). TNF-a also induces cell-specific damage to Schwann cells in vitro (Boyle et al, 2005) and thus contributes to the development of inflammatory neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Such molecules include TNF-α, IL-1β, interleukin-12 (IL-12), interleukin-2 (IL-2), interleukin-6 (IL-6), neopterin (a by-product of guanosine triphosphate metabolism produced by macrophages in response to lymphocyte activation), osteopontin, ICAM-1, E-selectin, IFN-γ, interleukin-18 (IL-18), matrix metalloproteinase 9 (MMP-9), vascular cell adhesion molecule-1 (VCAM-1), interleukin-1 receptor antagonist (IL-1RA), interleukin-37 (IL-37) α6β4 integrin (laminin receptor for Schwann cells and myelin) and vascular endothelial growth factor (VEGF) [96,28,53,93,76,7,44,72,42,117,122]. More recently, elevated plasma levels of interleukin-17 (IL-17) and interleukin-22 (IL-22) have been described in patients with GBS, with reduced levels seen following treatment with intravenous immunoglobulin [73,42].…”
Section: Introductionmentioning
confidence: 99%